THE ROLE OF THE TEACHER IN THE FORMATION OF THE STUDENT - CITIZEN WITHIN THE PUBLIC SCHOOL IN HIGH SCHOOL: A REFLECTION DONE FROM EXPERIENCES AS A RESIDENT IN THE PEDAGOGICAL RESIDENCE PROGRAM - Vieira, Miliane Moreira Cardoso; Souza Santos, Abimael Junior; Martins Aguiar Monteiro, Jaiara (DESAFIOS - Revista Interdisciplinar da Universidade Federal do Tocantins, 2020)
This work brings experiences lived in an Elementary School and High School, exposing the main difficulties in learning a new language and the challenges that English language teachers need to face in the exercise of the function, under the resident's gaze.